2017
DOI: 10.1038/oncsis.2017.84
|View full text |Cite
|
Sign up to set email alerts
|

Combination curcumin and (−)-epigallocatechin-3-gallate inhibits colorectal carcinoma microenvironment-induced angiogenesis by JAK/STAT3/IL-8 pathway

Abstract: Tumor microenvironment has a crucial role in cancer development and progression, whereas the mechanism of how it regulates angiogenesis is unclear. In this study, we simulated the colorectal carcinoma microenvironment by conditioned medium (CM) of colorectal carcinoma cell lines (SW620, HT-29, HCT116) supernatant or colorectal carcinoma tissue homogenate supernatant to induce normal endothelial cells (NECs). We found that colorectal carcinoma CM promoted tumor angiogenesis by coercing NECs toward tumor endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 44 publications
2
67
0
Order By: Relevance
“…15 Another previous study in our laboratory, mentioned above, showed the combination of UA + Res inhibited skin tumor promotion by TPA to a greater extent than either compound alone. 7 Jin et al 46 showed the combination of Curc and epigallocatechin-3-gallate (EGCG) suppressed colorectal carcinoma PDX tumor growth to a greater extent than either compound alone. Another study demonstrated the combination of luteolin and EGCG inhibited xenograft tumor growth of a head and neck squamous cell carcinoma cell line to a greater extent than either compound alone.…”
Section: Discussionmentioning
confidence: 99%
“…15 Another previous study in our laboratory, mentioned above, showed the combination of UA + Res inhibited skin tumor promotion by TPA to a greater extent than either compound alone. 7 Jin et al 46 showed the combination of Curc and epigallocatechin-3-gallate (EGCG) suppressed colorectal carcinoma PDX tumor growth to a greater extent than either compound alone. Another study demonstrated the combination of luteolin and EGCG inhibited xenograft tumor growth of a head and neck squamous cell carcinoma cell line to a greater extent than either compound alone.…”
Section: Discussionmentioning
confidence: 99%
“…EGCG potently inhibited BCR/ABL oncoprotein and the JAK2/STAT3/AKT pathway in BCR/ABL+ CML cell lines [7]. Curcumin worked synchronously with EGCG and considerably interfered with tumor conditioned media-induced transition of normal endothelial cells toward tumor endothelial cells by inhibition of the JAK/STAT3 signaling pathway [8].…”
Section: Targeting Of Jak/stat Signalingmentioning
confidence: 98%
“…Curcumin in combination with (−)-epigallocatechin-3-gallate markedly reduces tumor growth and microenvironmentinduced angiogenesis via modulation of the JAK/STAT3/ IL-8 pathway in colorectal carcinoma. 32 Treatment with resveratrol can downregulate angiogenesis via decreased expression of VEGF in the tumor microenvironment. 54 Berberine has been shown to reduce tumor-induced angiogenesis both in vitro and in vivo.…”
Section: Tcm Modulates the Tumor Microenvironmentmentioning
confidence: 99%